Recurence of myoma uteri after bilateral ligation of arteria uterina ascendens and after preoperative use of GnRH analogues - Sapmaz, E.; Gürateş, B.; Ayar, A. (My University, 2000)
OBJECTIVE: Effects of preoperative use of GnRH analogues and uterine arterial ligation technique on recurrence of uterine myomas were evaluated. STUDY DESIGN: Thirty patients with symptomatif uterine myoma were randomly divided into two groups (n= 15 vs n= 15). Patients in the first group were administered 3.6 mg goserelin (so9 monthly for three months prior to myomectomy. Bilateral uterine artery ligation in the same session with myomectomy for hemostasis were performed in the second group. RESULTS: Statistical difference couldn't be found in operative time, blood loss and number of enucleated myomas between two groups. A decrease in uterine volume about 30-50% at third postoperative month was recorded in GnRH analogue group (p=O.O01, Wilcoxon Rank) but myoma recurrence was also significantly higher (53% in GnRH agonist group, 13% in uterine artery ligation group, p=O.02, Fisher Exact test). DISCUSSION: A superiority of use GnRH analogues prior to abdominal myomectomy operations over "A. uterina ascendens " ligation couldn't be found. In fact, recurrence of myomas were significantly higher in that group. Because of this high recurrence rate and high cost of the treatment, preoperative GnRH analogue treatment was not found to be useful in momen with uterine myoma.
Abdominal myomektomi vakalarinda myom nüksü üzerine preoperatif GnRHa kullanimi ile uterin arterin asendan dalinin bilateral ligasyonunun etkinliginin karşllaştirilmasi
Keywords: Abdominal Myomectomy; Bilateral A. Uterina Ascendens Ligation; GnRHa; Myoma Recurrence